The Employee Relationship Analysis on Innovation Behavior of New Ventures Under the Organizational Psychology and Culture - Du, Sijin; Wang, Jianjun (Frontiers in Psychology, 2022)
The study aims to explore the psychology and behavior of employees in organizations in enterprise innovation. Based on the human resource management system (HRMS), organizational psychological ownership, and other related theories, the transformational leaders and their advice behavior in start-ups are taken as the research object. The data obtained from the questionnaire as the research samples. Second, the influence and intermediary effect of employees’ organizational psychological ownership on colleagues, leaders, and the whole enterprise are discussed, and the corresponding conclusions are drawn. The results show that the path coefficients of transformational leaders of start-up enterprises for employees’ advice to their superiors and their peers are 0.28 and 0.31, respectively, and p < 0.01. Therefore, transformational leadership has a positive impact on both elements. In the relationship between organizational psychological ownership and employee creativity, the r value is 0.34 and p < 0.01. This shows that organizational psychological ownership positively correlates with employees’ creativity. In addition, corporate support can mediate employees’ behavior and psychological ownership in the organization and has a positive correlation in support, identity, and care. Therefore, the impact of organization-employees relations on employees’ innovation behavior is discussed based on organizational psychology and culture, which can improve employees’ subjective initiative for work and provides ideas for the management and development of start-ups.